Prevalence of vaginal and cervical HPV infection among 35-year age cohort ever-married women in Kalutara district of Sri Lanka and the validity of vaginal HPV/DNA specimen as a cervical cancer screening tool: a cross-sectional study - KCM Perera; KN Mapitigama; HTCS Abeysena (BMC Infectious Diseases)
Abstract Background Cervical cancer is the 2nd most common female cancer among Sri Lankan females and is almost associated with sexually transmitted cervicovaginal human papillomavirus (HPV) infection. The study objectives were to determine the prevalence of vaginal and cervical HPV infection among 35year old ever-married women and assess the validity of primary healthcare provider-collected vaginal HPV/DNA specimens as a cervical cancer screening tool to improve the coverage of the programme. Method A descriptive cross-sectional study was carried out from the 1st of September 2018 to the 31st of January 2019. Ever-married women 35 years of age in Kalutara district were the study population. Two women from each Public Health Midwife area (n = 413) were selected randomly from the relevant area eligible families register/s. HPV/DNA cervical specimen and vaginal specimen collection (n = 621) were carried out. Specimens were screened by the Cobas 4800 HPV/DNA automated Polymerase Chain Reaction (PCR) machine. Participants’ profiles were recorded by the research assistants using an interviewer-administered questionnaire. Results The overall prevalence of vaginal and cervical HPV infection was 7.08% (95% CI; 5.2-9.4%) and 6.12% (95% CI; 4.26-8.3%) respectively. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), diagnostic accuracy, and the kappa coefficient of the vaginal HPV/DNA screening method vs. cervical HPV/DNA screening method were 100%, 98.9%, 86.4%, 100%, 99% and 0.92 respectively. Conclusions Vaginal HPV/DNA specimen screening method can be used as a cervical cancer screening tool due to its high validity. Pilots of the feasibility should be set up before the regional or national rollout of vaginal sampling strategies.